Reassessing the Implementation of Murābaḥah Contracts in Islamic Financial Institutions: Legal, Ethical, and Operational Challenge - Sudarman; Amalia S. Tapparang; Sophie Miller (PT. Islamic Research Publisher, 2024)
Murābaḥah contracts constitute one of the most widely used financing instruments in Islamic financial institutions and are designed to provide a Sharia-compliant alternative to conventional credit-based transactions. Despite their dominance in Islamic banking practices, growing concerns have emerged regarding their legal compliance, ethical implications, and operational efficiency. This study aims to reassess the implementation of murābaḥah contracts by critically examining their legal, ethical, and operational challenges and by exploring strategies for reform that align these contracts with the objectives of Islamic law (Maqāṣid al-Sharī‘ah). The research adopts a qualitative research design employing a mixed qualitative approach that integrates systematic literature review, case studies from Islamic financial institutions across different regions, and semi-structured interviews with Islamic finance experts, practitioners, and regulators. Data were analyzed using thematic analysis and comparative analysis to identify recurring patterns and discrepancies in murābaḥah implementation across institutional contexts. The findings reveal three major challenges. First, legal challenges arise from inconsistencies in Sharia compliance and regulatory ambiguities, particularly concerning ownership transfer, agency arrangements, and the continued reliance on interest-based benchmarks for determining profit margins. Second, ethical challenges are reflected in the partial realization of Maqāṣid al-Sharī‘ah, where murābaḥah financing often prioritizes consumptive lending rather than promoting justice, social welfare, and productive economic development. Third, operational challenges include complex documentation procedures, high transaction costs, and institutional overdependence on murābaḥah financing, commonly described as the “murābaḥah syndrome.” The study further identifies the need for comprehensive reforms, including the reformulation of murābaḥah products, diversification toward partnership-based financing models, strengthening of regulatory frameworks, and the integration of financial technologies to improve transparency and compliance. This study contributes to the literature on Islamic finance by offering a holistic framework for reassessing murābaḥah practices and by proposing practical strategies to enhance their alignment with Islamic ethical principles and sustainable economic development.